Atypical ocular Chelonoid herpesvirus manifestations in a captive Loggerhead turtle (Caretta caretta). (14th October 2020) - Oriá, Arianne P.; Silva, Danielle N.; Raposo, Ana Cláudia; Estrela‐Lima, Alessandra; Pires, Thaís T.; Gattamorta, Marco A.; Zamana, Roberta R.; Matushima, Eliana R.; Ofri, Ron
Abstract: A captive loggerhead turtle ( Caretta caretta ) of unknown sex, 3 years of age, presented with bilateral mucoid secretions, severe chemosis, conjunctival hyperemia, and globe retraction. The animal was evaluated ophthalmologically and systemically, and hematological, microbiological, and conjunctival cytological and biopsy samples were collected for complementary diagnosis. The histopathological examination showed amphophilic intranuclear inclusions associated with severe inflammatory infiltrate. The diagnosis of Chelonid alphaherpesvirus 5 (ChAHV 5) was confirmed with end point PCR. Following systemic treatment with L‐lysine, acyclovir and vitamin A, the ocular signs resolved. No amphophilic intranuclear inclusions were seen in a follow‐up biopsy 5 months later, and there has been no recurrence of clinical ophthalmic signs during a 4‐year follow‐up. It is suggested that ChAHV 5 be considered as a differential diagnosis in captive marine turtles that present for conjunctival disease other than fibropapillomatosis.